Geophysical model functions for cold water microwave radiation dependency on wind speed in K and Ka range at an incidence angle of 55° - Zabolotskikh, E.v.; Chapron, Bertrand (Sovremennye problemy distantsionnogo zondirovaniya Zemli iz kosmosa, 2019)
Geophysical model functions (GMFs) of the ocean microwave radiation dependence on wind speed at the frequencies of K and Ka range for an incidence angle of 55° are derived using the measurements of the satellite microwave radiometer Advanced Microwave Scanning Radiometer 2 (AMSR2) over open Arctic ocean at the sea surface temperatures (SST), not exceeding 10 °C. To estimate ocean radiation coefficients, surface microwave radiation was calculated using physical modeling of the ocean – atmosphere system brightness temperature. The simulation results made it possible to estimate surface radiation at 18.7, 23.8 and 36.5 GHz on the vertical and horizontal polarization with known atmospheric parameters, based on the ERA-Interim reanalysis data. These estimates were matched to the sea surface wind speeds (V), retrieved by applying previously developed V retrieval algorithm to the AMSR2 measurements at 6.9 and 10.65 GHz. The resulting GMF were compared to a widely used published model. A more significant dependence of the GMFs on SST is found: at SST < 4 °C, differences in the GMFs are not observed, but at 4 < SST < 10 °C the sensitivity of the emissivity to V drops with the SST increase for all the frequencies at horizontal and vertical polarization. The resulting regression lines have a positive slope. The sensitivity of a horizontally polarized signal to sea surface wind speed is more than 2 times higher than the sensitivity of a vertically polarized signal.